Expression of hypoxia‐inducible factor‐1α, vascular endothelial growth factor and prolyl hydroxylase domain protein 2 in cutaneous squamous cell carcinoma and precursor lesions and their relationship with histological stages and clinical features. Issue 1 (20th December 2013) - An, Xiangjie; Xu, Guangfen; Yang, Liu; Wang, Yuejue; Li, Yan; Mchepange, Uwesu O.; Shen, Guanxin; Tu, Yating; Tao, Juan
Abstract The hypoxia‐inducible factor‐1 (HIF‐1α) pathway is associated with tumor growth, angiogenesis and metastasis in various carcinomas. Little is known regarding the role of the HIF‐1α signaling pathway in cutaneous squamous cell carcinoma (SCC). We investigated the expression of HIF‐1α, vascular endothelial growth factor (VEGF) and the HIF negative regulator, prolyl hydroxylase domain protein 2 (PHD2), in cutaneous SCC, Bowen's disease, seborrheic keratosis (SK) and normal skin by immunohistochemistry and in situ hybridization. Additionally, we explored the relationships between these factors and the clinical and histological characteristics of each disease. Our study indicated that the expression of HIF‐1α and VEGF was significantly higher (P < 0.05) in cutaneous SCC than in Bowen's disease, SK or normal skin. In contrast, PHD2 showed significantly higher expression in normal skin compared with SK, Bowen's disease and cutaneous SCC (P < 0.05). Grade II–IV cutaneous SCC had higher expression levels of nuclear HIF‐1α and cytoplasm VEGF protein but less nuclear PHD2 protein than grade Ι cutaneous SCC (P < 0.05). Overexpression of HIF‐1α and VEGF, as well as the decreased expression of PHD2, may play important roles in the development of cutaneous SCC.